Liver damage and immune responses - Hackstein, Carl-Philipp (Zeitschrift für Gastroenterologie, 2025)
Chronic liver disease (CLD) has massive systemic repercussions including major impacts on the body’s immune system. Abnormalities in phenotype, function and numbers of various immune cell subsets have been established by a large number of clinical and pre-clinical studies. The loss of essential immune functions renders CLD-patients exceptionally susceptible to bacterial and viral infections and also impairs the efficacy of vaccination. Consequently, infections represent a major clinical issue causing significant morbidity and mortality in these patients. Mechanistically, the immune dysfunction associated with CLD results from the increased translocation of bacteria and bacterial cues from the intestine. These trigger a signaling axis around the cytokines IFN I and IL-10 in hepatic myeloid cells, which aside from impairing the function of the myeloid cells themselves, also has notable negative impacts on the functionality of other immune cells. T cells in CLD-patients and -models are especially affected by this signaling axis and display a variety of quantitative and qualitative defects. Due to the high clinical relevance, understanding the mechanisms underlaying CED-associated immune dysfunction is of critical importance to discover and develop new therapeutic targets.
Keywords: Liver; gut; chronic liver disease; microbial translocation; CAID; type I interferon; interleukin 10